2013
DOI: 10.7763/ijfcc.2013.v2.232
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Defect Management Process Model for Software Quality Improvement

Abstract: Abstract-Defect remains in the whole life of software because software is developed by humans and 'to err is human'. The main goal of well-organized software defect management process is to produce quality software with the least number of defects to reduce the impact of problems in the organization. Defect management process includes three levels which are defect detection, defect analysis and defect prevention to eliminate and mitigate the potential defects. At first level test the software work product unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Personnel module has four submodules, the sub-modules of employees, salaries submodules, submodules on leave, and the submodule stops working. (Bassil, 2012;Cahyono, 2010;Christian, 2014;Febriadi & Zamsuri, 2017;Khan, 2013;O'brien, 2000) CONCLUSIONS (Agus, F, & Yunanto, 2010) After completing the design and manufacturing information system application design agroindustrial of Jamu Madura, it could be concluded that the design of information systems agroindustrial of Jamu Madura require ten entities that leave the table, employee table, the table stops working, the tables products, sales detail table, the table of salaries, other expenses table, another entry table, table sales note and table production records. Each entity has a data type that has been tailored to the needs of data and linked with other entities that have relevance to make the system completely.…”
Section: Methodsmentioning
confidence: 99%
“…Personnel module has four submodules, the sub-modules of employees, salaries submodules, submodules on leave, and the submodule stops working. (Bassil, 2012;Cahyono, 2010;Christian, 2014;Febriadi & Zamsuri, 2017;Khan, 2013;O'brien, 2000) CONCLUSIONS (Agus, F, & Yunanto, 2010) After completing the design and manufacturing information system application design agroindustrial of Jamu Madura, it could be concluded that the design of information systems agroindustrial of Jamu Madura require ten entities that leave the table, employee table, the table stops working, the tables products, sales detail table, the table of salaries, other expenses table, another entry table, table sales note and table production records. Each entity has a data type that has been tailored to the needs of data and linked with other entities that have relevance to make the system completely.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, bug maintenance tasks concentrate on needs and need for growth. Whenever the computer software production levels are functional, it will minimize the time and overhead to deliver a high-quality product (Khan, 2013). The avoidance of defects will improve both high quality and productivity if the number of defects treated decreases, the consistency increases (Suma and Gopalakrishnan Nair, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%